2018
DOI: 10.1139/cjpp-2017-0228
|View full text |Cite
|
Sign up to set email alerts
|

NMDA receptors in the dorsal hippocampal area are involved in tramadol state-dependent memory of passive avoidance learning in mice

Abstract: The precise neurobiological mechanisms of tramadol abuse underlying the cognitive function are still unknown. The aim of the present study was to examine the possible effects of intra-CA1 injections of N-methyl-d-aspartate (NMDA), a glutamate NMDA receptor (NMDAR) agonist, and d,l-2-amino-5-phosphonopentanoic acid (DL-AP5), a competitive NMDAR antagonist, on tramadol state-dependent memory. A single-trial step-down passive avoidance task was used for the assessment of memory retrieval in adult male NMRI mice. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…On the other hand, our previous studies and those of other investigators have revealed that both consolidation and retrieval of one-trial avoidance are regulated by CA1 μ-opioid receptors, CA1 alpha-2 receptors, CA1 muscarinic ACh receptors, CA1 CB1 receptors, CA1 GABA-A receptors and 5HT1A receptors, and require both activity of CAMKII, ERK, PKA and CREB in the hippocampus and in other brain regions (Izquierdo et al, 2006;Jafari-Sabet, 2011;Jafari-Sabet and Karimi, 2017;Jafari-Sabet et al, 2013, 2018a, 2018bMahgoub et al, 2006;Phelps, 2004;Zarrindast et al, 2006).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…On the other hand, our previous studies and those of other investigators have revealed that both consolidation and retrieval of one-trial avoidance are regulated by CA1 μ-opioid receptors, CA1 alpha-2 receptors, CA1 muscarinic ACh receptors, CA1 CB1 receptors, CA1 GABA-A receptors and 5HT1A receptors, and require both activity of CAMKII, ERK, PKA and CREB in the hippocampus and in other brain regions (Izquierdo et al, 2006;Jafari-Sabet, 2011;Jafari-Sabet and Karimi, 2017;Jafari-Sabet et al, 2013, 2018a, 2018bMahgoub et al, 2006;Phelps, 2004;Zarrindast et al, 2006).…”
Section: Discussionmentioning
confidence: 75%
“…It is well established that CA1 regions of the hippocampus are crucial for memory formation (Ranganath, 2019) and also memory consolidation and retrieval in one-trial inhibitory avoidance (Izquierdo et al, 2006; Jafari-Sabet, 2006; Jafari-Sabet et al, 2013, 2018a, 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…NMDARs present on the presynaptic and postsynaptic membrane bound with glutamate released from presynaptic terminals to regulate synaptic plasticity [6,13]. NMDARs are composed of NR1 and NR2 or NR3 subunits, among which NR2A and NR2B play key roles in activity-dependent synaptic plasticity [51]. Wang H [23] studied the effects of 2.856 GHz radiation with an average power density of 2.5, 5 or 10 mW/cm 2 for 6 min/day (5 d/week, up to 6 weeks) on NMDARs expressions and phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, variations of this balance in each direction can potentiate state-dependent memory. For instance, cholinergic signalings of state-dependent memory involved both inhibiting cholinergic activity by scopolamine and growing cholinergic activity by physostigmine (Jafari-Sabet et al, 2018[ 31 ]). Additionally, opiates support state-dependent memory and of all types of opioid receptors, morphine stimulated µ-receptors to appear to be the maximum effective (Zarrindast et al, 2006[ 87 ]).…”
Section: Molecular Mechanisms Of State-dependent Memorymentioning
confidence: 99%